Trust, positive reciprocity, and negative reciprocity: Do these traits impact entrepreneurial dynamics? - Marco Caliendo; Frank Fossen; Alexander Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Experimental evidence reveals that there is a strong willingness to trust and to act in both positively and negatively reciprocal ways. So far it is rarely analyzed whether these variables of social cognition influence everyday decision making behavior. We focus on entrepreneurs who are permanently facing exchange processes in the interplay with investors, sellers, and buyers, as well as needing to trust others and reciprocate with their network. We base our analysis on the German Socio-Economic Panel and recently introduced questions about trust, positive reciprocity, and negative reciprocity to examine the extent that these variables influence the entrepreneurial decision processes. More specifically, we analyze whether i) the willingness to trust other people influences the probability of starting a business; ii) trust, positive reciprocity, and negative reciprocity influence the exit probability of entrepreneurs; and iii) willingness to trust and to act reciprocally influences the probability of being an entrepreneur versus an employee or a manager. Our findings reveal that, in particular, trust impacts entrepreneurial development. Interestingly, entrepreneurs are more trustful than employees, but much less trustful than managers.
Keywords: D81; J23; M13; L26; 330; Entrepreneurship; trust; reciprocity